2022
DOI: 10.1091/mbc.e21-03-0128
|View full text |Cite
|
Sign up to set email alerts
|

Signed, sealed, and delivered: RNA localization and translation at centrosomes

Abstract: Protein localization is intrinsic to cellular function and specialized activities, such as migration or proliferation. Many localized proteins enrich at defined organelles, forming subdomains of functional activity further specified by interacting protein assemblies. One well-studied organelle showing dynamic, functional changes in protein composition is the centrosome. Centrosomes are microtubule-organizing centers with diverse cellular functions largely defined by the composition of the pericentriolar materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Also among the DIFFRAC hits were many proteins with known roles in protein synthesis, in particular, many subunits of the tRNA multi-synthetase complex, translation elongation factors and ribosomal proteins (Fig S2), These data suggest the possibility that IFT-A, like other ciliopathy proteins (Morleo et al, 2022), may play a broader role in proteome regulation. These results encourage further study to determine whether IFT-A contributes to localized translation that has been proposed to occur at either basal bodies (Lerit, 2022) or within cilia (Hao et al, 2021).…”
Section: Detection Of Proteins Significantly Altered In Ift122 Mutantsmentioning
confidence: 65%
“…Also among the DIFFRAC hits were many proteins with known roles in protein synthesis, in particular, many subunits of the tRNA multi-synthetase complex, translation elongation factors and ribosomal proteins (Fig S2), These data suggest the possibility that IFT-A, like other ciliopathy proteins (Morleo et al, 2022), may play a broader role in proteome regulation. These results encourage further study to determine whether IFT-A contributes to localized translation that has been proposed to occur at either basal bodies (Lerit, 2022) or within cilia (Hao et al, 2021).…”
Section: Detection Of Proteins Significantly Altered In Ift122 Mutantsmentioning
confidence: 65%
“…The centriole inserts into the base of the nucleus to become the basal body, which then seeds the growth of the sperm axoneme. The recent results revealing a local centrosome proteins synthesis (Bergalet and Lecuyer, 2014;Bergalet et al, 2020;Lerit, 2022) helped us to suggest gNAC involvement in centrosome proteostasis which in mammalian centrosomes is thought can be related to the functioning of mysterious, so-called centrosome satellites particles (Renaud and Bidere, 2021). At the posterior pole of the embryo, at the germ plasm location, the forming pole buds and pole cells were shown to contain cytoplasmic gNAC accumulated along microtubules of mitotic asters and as the small islands around the centriole.…”
Section: Discussionmentioning
confidence: 99%
“…We propose two functional significances of gNAC presence in the centrosomes. The first can be applied to gNAC, which can be considered as a direct component involved in the centrosome local protein synthesis, the signs of which existence have been convincingly demonstrated in a number of papers (Bergalet et al, 2020; Safieddine et al, 2021) and widely discussed (Besse and Ephrussi, 2008; Medioni et al, 2012; Chouaib et al, 2020; Lashkevich and Dmitriev, 2021; Lerit, 2022). The centrosome proteome encompassing the hundreds of proteins is proposed to use in mammals the so called centriolar satellite granules surrounding centrosome that are hypothesized as the participants of proteostasis network, but up to date their functions remain mysterious (for review, (Renaud and Bidere, 2021)).…”
Section: Discussionmentioning
confidence: 99%
“…Localization of mRNA constitutes an efficient mechanism for spatial control of organelle proteomes and cellular functions (Buxbaum et al, 2015;Lécuyer et al, 2007;Ryder and Lerit, 2018). The C/BB has been known to harbor RNA molecules (Alliegro, 2011;Hoffman, 1965;Lerit, 2022;Marshall and Rosenbaum, 2000;Rieder, 1979) transported via the cytoskeleton (Das et al, 2021), but the identity and functions of these RNAs are not fully known. Although more evidence exists for the localization of mRNAs (Blower et al, 2007;Lambert and Nagy, 2002;Lécuyer et al, 2007;Zein-Sabatto and Lerit, 2021), RBPs, ribosomal proteins and translation factors (Müller et al, 2010;O'Neill et al, 2022) at the centrosome, proteomic surveys have revealed that the cilium-BB is also enriched for mRNAs and the protein synthesis machinery (Fingerhut and Yamashita, 2020;Hao et al, 2021;Jao et al, 2017;Kwon et al, 2021).…”
Section: Mrna Localization and Translationmentioning
confidence: 99%